2019
DOI: 10.1186/s12998-018-0230-y
|View full text |Cite
|
Sign up to set email alerts
|

Managing sickness absence of patients with musculoskeletal pain – a cross-sectional survey of Scandinavian chiropractors

Abstract: BackgroundMusculoskeletal pain is a major cause of work disability. Many patients with musculoskeletal pain seek care from health care providers other than their general practitioners, including a range of musculoskeletal practitioners. Therefore, these musculoskeletal practitioners may play a key role by engaging in sickness absence management and work disability prevention. This study aimed to determine the prevalence of musculoskeletal practitioners’ practice behaviours, and their perceptions and beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved. This unresolved issue creates confusion for stakeholders and threatens to impede professionalization and cultural authority.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved. This unresolved issue creates confusion for stakeholders and threatens to impede professionalization and cultural authority.…”
Section: Discussionmentioning
confidence: 96%
“…disability prevention both informally and as part of system-supported pathways [6,7]. Another example of chiropractors functioning in interprofessional collaboration was provided by Wirth et al who reported on outcomes and trajectories of patients referred from a surgical department to chiropractic care [8].…”
Section: Commentarymentioning
confidence: 99%